The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1590/s0103-84782007000600002
|View full text |Cite
|
Sign up to set email alerts
|

Efeito dos extratos aquoso e oleoso de Nim [Azadirachta indica A. Juss (Meliaceae)] na produção de patulina em maçãs contaminadas por Penicillium expansum

Abstract: RESUMO A Região Sul do

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…Several assays with other fungi and toxins have shown similar results. Fungitoxic effects indicate that Neem extracts block the biosynthesis pathway of aflatoxin in Aspergillus parasiticus [31]; citrinin in Penicillium citrinum [35]; penicillic acid in Penicillium cycplopium [33]; patulin in Penicillium expansum in vitro [34] and in contaminated apples [32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several assays with other fungi and toxins have shown similar results. Fungitoxic effects indicate that Neem extracts block the biosynthesis pathway of aflatoxin in Aspergillus parasiticus [31]; citrinin in Penicillium citrinum [35]; penicillic acid in Penicillium cycplopium [33]; patulin in Penicillium expansum in vitro [34] and in contaminated apples [32].…”
Section: Resultsmentioning
confidence: 99%
“…The Neem (Azadirachta indica A. Juss) is a denseleaved tree of the Meliaceae family whose biologically active extracts are obtained from its leaves, seeds, fruits and trunk, with acknowledged multiple therapeutic, insecticide, nematicide, anti-microbial and fungicide qualities [24][25][26]. Several studies show that Neem water and oil extracts are toxic to fungi [27][28][29][30][31] and may result in the reduction or inhibition of mycotoxin production [32][33][34][35][36]. Great interest exists in verifying the effects of the plant's extract on the fungi Fusarium oxysporum f. sp.…”
Section: Introductionmentioning
confidence: 99%
“…Os resultados se assemelham aos apresentados neste trabalho, pois para estudos empregando o etanol como extrator, os efeitos de MIC não são promissores. Outros autores ainda reafirmam a baixa ação de extratos etanólicos de neem frente a fungos tais como (ARROTEIA; MACHINSKI, 2007).…”
Section: Discussionunclassified
“…Inúmeras substâncias com atividade antibacterianas foram isoladas ao longo da história, dentre eles os óleos essenciais, os terpenos, triterpenos e flavonoides (DI STASI, 1996;BRASIL, 2002;SUBAPRIYA et al, 2005;SUBRA-MANIAN et al, 2005;CORDEIRO et al, 2006). Mediantede vias metabólicas secundárias os vegetais podem produzir alcaloides, flavonoides, isoflavonoides, taninos, cumarinas, glicosídeos, terpenos (CECHINEL FILHO;YUNES, 1998;ARROTEIA et al, 2007). Várias espécies de plantas têm sido pesquisadas em relação a produção dos terpenoides (CAN-TRELL et al, 2001) e fisalinas (PIETRO et al, 2000;JA-NUÁRIO et al, 2002).…”
Section: Introductionunclassified
“…Extracts from neem (Azadirachta indica A. Juss), employed in pest control in plant cultures, (15,20) reveal bioactive substances in all parts of the tree, especially in its seeds (12). It has been shown that neem seeds oil has fungitoxic effects (10), whereas in vitro investigations revealed the inhibitory effects of neem extracts in the production of several mycotoxins (1,5,13,14). Results show that the production of ZEA in neem-less medium (control) was higher than that in extracts with NO (tests) ( Figure 1 and Table 1).…”
mentioning
confidence: 94%